MicroRNA-365 Inhibits Vascular Smooth Muscle Cell Proliferation through Targeting Cyclin D1 - Zhang, Peng (Ivyspring International Publisher, 2014)
MicroRNA-365 (miR-365) plays crucial roles in regulating cell proliferation, apoptosis and differentiation in various cell types. However, its function in vascular smooth muscle cells (VSMCs) is largely unknown. In our study, we found miR-365 was highly expressed in adult rat carotid arteries, but was significantly decreased in rat carotid arteries after balloon injury, a process involving neointima formation and VSMC proliferation. In vitro, the miR-365 significantly inhibited cell proliferation of isolated primary rat aortic VSMCs. Furthermore, we identified that cyclin D1 was a direct target of miR-365 in VSMCs. The miR-365 suppressed cyclin D1 expression on both mRNA and protein level. Luciferase reporter assay demonstrated that miR-365 inhibited cyclin D1 through targeting its 3'UTR. Importantly, cyclin D1 overexpression rescued the inhibitory effect of miR-365 on VSMCs proliferation. Taken together, by our studies, we identified a new MicroRNA, miR-365, involving in the pathological process of vascular injury, which inhibits VSMC proliferation through targeting cyclinD1.